2015
DOI: 10.12913/22998624/59085
|View full text |Cite
|
Sign up to set email alerts
|

Inproving of the Quality Food for Animals by Pulsed Power Plasma Discharge

Abstract: Soy beans powder mixed with water is a good food for animals. However, there are two problems with this brew. One is that soy beans powder is sunk down to fast. Parts of soy beans powder are too big and too heavy. Animals do not eat soy beans powder because after a few minutes (around 3min) is sunk down and soy beans are on the bottom case. Another negative point is a quick growth of mold, especially during summer when the temperature is highest. Mold is making food unhealthy and causes unpleasant smell. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…During these studies, decreases in concentration were observed [17][18][19]. The rotating electrode is not responsible for phenomenon phenomena, also observed in reactors of other types [20][21][22][23]. The factor that determined the investigations of electrodes used in the plasma reactor was the decreasing efficiency of the device during ozone production while maintaining constant process parameters [24].…”
Section: Methodsmentioning
confidence: 93%
“…During these studies, decreases in concentration were observed [17][18][19]. The rotating electrode is not responsible for phenomenon phenomena, also observed in reactors of other types [20][21][22][23]. The factor that determined the investigations of electrodes used in the plasma reactor was the decreasing efficiency of the device during ozone production while maintaining constant process parameters [24].…”
Section: Methodsmentioning
confidence: 93%
“…Gnapowski et al [ 87 ] also attempted to improve the properties of soybean powder (SBP) suitable as a good food for animals. However, there are two problems with this brew.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…As a result of flexible collisions between the migrating charged particles and inert air particles, the neutral ones increase their rate, causing an "Electric wind" that takes place in close proximity to the surface [6]. The operation of the plasma actuator depends on many factors, among others; dielectric type [5,7], power supply system (voltage, frequency, pulse width), air flow speed, geometry [2,3] and number of electrodes [9].…”
Section: The Use Of Dbd Barrier Discharges To Control the Flow Of Thementioning
confidence: 99%